Upscaling Above-ground Biomass Using Radar Remote Sensing data - Hashim, Mazlan (National Institute for Environmental Studies, Japan, 2006)
Relatively large spatial in-situ information collected from mainly three plots of primary, secondary and fragmented forests in the collaborative research period have been the main source of input in mapping, detecting and monitoring of changes biophysical parameters within Pasoh Forest Region (PFR). The main aim of the study have been focused at utilizing satellite remote sensing data together with GIS and related ecological models for risk assessments due to the landscape development within the stipulated time period. Multi-temporal satellite remote sensing data have been used to detailed mapping of the landscape changes and its related impact, among others have been the input in mapping ecology services value and goods (ESVG), total above-ground biomass (TAGB) and analysis of soil loss due to these changes. Remote sensing is often the only practical and cost-effective means in deriving information over large area, however issues in maintaining the accuracy needed for specific application can be validated using known ground truth source, such as information generated from PFR studies. The on-going task of study undertaken within the mapping context concern with up-scaling the ESVG to cover the entire Peninsular. In the initial phase of the study Synthethic Aperture Radar (SAR) data of JERS-1 and Radarsat have been utilized to form the base for TAGB extraction to enable carbon estimation. Risk assessments and impacts due to landscape development have been confined to forest water yield and erosion, up-scaling being undertaken within catchments of Pahang River assimilating results of study on Triang River catchment. Preliminary results of the tasks undertaken in upscaling TAGB is highlighted in this presentation, emphasizing on status and constraints faced in consideration of the operational level and future requirements of the end output.